2019
DOI: 10.2217/pgs-2018-0178
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of CYP2C19 and CYP4F2 Variants and Clinical Factors on Treatment Outcomes During Antiplatelet Therapy

Abstract: Aim: The aim of this study was to determine the impact of genetic and nongenetic factors on treatment outcomes in patients receiving dual antiplatelet therapy after percutaneous coronary intervention and stent implantation. Materials & methods: Patients (n = 628) used clopidogrel or ticagrelor for at least 1 week before platelet aggregation test. Results: Multivariate binary regression analysis demonstrated that aspirin use and CYP4F2 T allele significantly increased odds for bleeding in clopidogrel users … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 40 publications
2
19
2
Order By: Relevance
“…According to Kupstyte et al [42], the CYP4F2 AA variant is associated with early stent thrombosis. In another work, where the CYP4F2 rs3093135 polymorphism was studied, it was shown that the T allele was independently associated with bleeding during dual antiplatelet therapy [15]. Here, we also showed that the CT+TT allele variant of the CYP4F2 polymorphic marker C(Val433Met) T is associated with an increased risk of bleeding on anti-thrombotic therapy, which is consistent with the study of Kupstyte et al [42].…”
Section: Discussionsupporting
confidence: 92%
“…According to Kupstyte et al [42], the CYP4F2 AA variant is associated with early stent thrombosis. In another work, where the CYP4F2 rs3093135 polymorphism was studied, it was shown that the T allele was independently associated with bleeding during dual antiplatelet therapy [15]. Here, we also showed that the CT+TT allele variant of the CYP4F2 polymorphic marker C(Val433Met) T is associated with an increased risk of bleeding on anti-thrombotic therapy, which is consistent with the study of Kupstyte et al [42].…”
Section: Discussionsupporting
confidence: 92%
“…However, among the 10 candidate SNPs, only P2Y12 (rs6787801 and rs6785930) showed a statistically significant but not clinically relevant effect on ticagrelor levels and bleeding events (Table 4), which was in agreement with the literature. [17][18][19][20] At present, several optimal potency and duration of DAPT were proposed, given the unique features of East Asian patients during antiplatelet therapy. 34,35 Notably, low-dose ticagrelor (60 mg BID) appeared to have a good safety/efficacy profile but numerically lower bleeding events than the standard dose (90 mg BID).…”
Section: F I G U R E 5 Relationship Between Ticagrelor Trough Concent...mentioning
confidence: 99%
“…18,19 Additionally, Tatarunas et al identified variants in CYP4F2, a cofactor essential for blood clotting by regulating the bioavailability of vitamins E and K, were significantly associated with bleeding events during dual antiplatelet therapy (DAPT). 20 Therefore, this study aimed to investigate the relationship between bleeding events and plasma concentrations of ticagrelor and AR-C124910XX in Chinese ACS patients with DAPT. Meanwhile, the effect of 10 SNPs on ticagrelor concentrations and bleeding events was also investigated, including CYP3A5*3 (rs776746), CYP3A4*1G (rs2242480), SLCO1B1 (rs12371604 and rs113681054), PEAR1 (rs12566888, rs12041331 and rs4661012), P2Y12 (rs6785930 and rs6787801) and CYP4F2 (rs3093135).…”
mentioning
confidence: 99%
“…Loss-of-function alleles CYP2C19*2 and CYP2C19*3 decreased activity of the metabolites by affecting functional metabolites of the enzyme, leading to a high platelet response. Patients with CYP2C19*17 [ 29 ] and CYP4F2 T alleles [ 135 ] were at higher risk of bleeding. The PLATO study found that ticagrelor was superior to clopidogrel in reducing cardiovascular composite endpoints in all CYP2C19 genotypes.…”
Section: Special Groupsmentioning
confidence: 99%